Potential of Biduri Fiber (Calotropis gigantea) as Material for Oil Spill Absorbent - Sukmawati, Anne; Septiani, Wulan (Journal of Materials Exploration and Findings, 2023)
Biduri fiber (Calotropis gigantea) is a natural hollow fiber with hydrophobic and oleophilic properties potentially used as oil spilled sorbent from seawater. This study aims to determine the absorption capacity and efficiency of the Biduri fiber and membrane to fuel oil. Measurement of oil absorption to seawater was carried out at various fiber weights (0.5-1.5 g), fiber composition (50-95%), contact time (10-90 minutes), temperature (30 and 50°C), and compared with commercial products. The results showed that the fiber weight variation of 0.5-1.5 g has an average absorption efficiency of 96.67%, and the highest absorption was obtained in a weight of 0.5 g, a density of 0.0143 g/cm3, 43.79 g/g. In the membrane composition of 50-95%, the absorption efficiency of 96.98%, and the highest absorption capacity of the membranes was 95%, density of 0.0259 g/cm3 and 44.62 g/g. The absorption capacity and efficiency of Biduri fiber and membrane are higher than commercial products.